Início precoce versus tardio de movimentação livre de membros superiores no pós-operatório de câncer de mama e reconstrução imediata: impacto na recuperação cinético-funcional e nas complicações cicatriciais - Rizzi, Samantha Karlla Lopes De Almeida [UNIFESP] (2019)
Introduction: Physical therapy is important for prevention of motor and functional complications after breast cancer surgery, especially when started early, with restoration of motor function and improvement of patients' quality of life. However, there is no prospective randomized study on different physiotherapeutic treatments in patients undergoing mastectomy and immediate alloplastic reconstruction. Objectives: To evaluate the impact of upper limb free exercise released 15 or 30 days after surgery on shoulder range of motion (ROM), pain and limb function; on the incidence of dehiscence, seroma, infection and necrosis; and in need of reoperations of patients after mastectomy and immediate reconstruction with alloplastic material. Methods: Sixty women after mastectomy for breast cancer surgery were included in a randomized controlled trial. They underwent preoperative evaluations and 07, 15, 30, 60 and 90 days after surgery. They started exercises, with shoulder range of motion limited to 90º, the day after surgery and were instructed to perform at home. After two weeks, they were randomized into two groups of 30 patients: “Free Amplitude Group” - release of shoulder joint amplitude at the pain limit or until the surgical edges were detached, and “Limited Amplitude Group” - maintenance of shoulder movement restriction at 90º until 30 days after the surgery, at which time they were also released to free range exercises. Results: Patients with free upper limb exercise release after 15 days of surgery had less pain, greater shoulder amplitude and better upper limb function, compared to those who had restricted movement at 90º for 30 days, with no increased incidence or prevalence of postoperative scarring complications, and without interference with the need for reoperations . Conclusion: Postoperative protocol with free shoulder ROM released after 15 days of surgery is safe and beneficial for kinetic-functional recovery and pain control of patients after mastectomy and immediate reconstruction with alloplastic material for breast cancer.